Utilisation of sniffer rats as a novel screening technique to accelerate remediation of contaminated soil - Kean, Donna; Lugundi, Bakari; Mshana, Said; Magesa, Walter; Schneider, Miriam; Segal, Daniel C.; Cox, Christophe; Fast, Cynthia D. (Frontiers in Environmental Science, 2026)
IntroductionSoil contaminated with petroleum hydrocarbons (PHCs) poses a major environmental threat, contributing to soil degradation, vegetation loss and broader ecological risks. Yet a major bottleneck in remediation remains the reliable identification of affected areas. Existing methods for delineating PHC-contaminated soil, such as portable instruments and canine teams, are labour intensive, costly, and delayed by logistical challenges.MethodsWe trained African giant pouched rats (Cricetomys ansorgei) in a laboratory environment to perform on-site style screening of soil samples.ResultsAfter explicit training to delineate soils at a regulatory-relevant threshold of 0.50%, rats reached an overall sensitivity of 100% and specificity of 98.9% individually, and a team-based strategy of six rats achieved perfect discrimination, correctly identifying all PHC-positive samples while rejecting all clean soils. Performance was not significantly affected by crude oil source or background soil variation, including samples from active remediation sites.DiscussionThese results provide the first evidence of threshold-sensitive PHC detection by any species, demonstrating rats’ potential as a rapid, low-cost, and scalable complement to existing techniques. Future work should evaluate deployment of trained rat teams in field conditions and explore integration into mobile testing units.